"Maybe it's kind of normal to hear voices": The role of spirituality in making sense of voice hearing. Issue 1 (2nd January 2020) - Lewis, Sophie Hannah; Sanderson, Chris; Gupta, Anjula; Klein, Claire
ABSTRACT: First-person accounts of voice hearing are scarce. This research aims to explore the role of spirituality in the sense-making process of hearing voices. Five semistructured interviews explored experiences of spirituality and hearing voices. Qualitative data was analyzed using interpretive phenomenological analysis (IPA). Three superordinate themes were identified: need for connection, values about self and identity, and making sense. The findings suggest a relationship between spirituality and voice hearing, and relate to the need for belongingness and self-identity. Acknowledging the sense making process and engaging in conversations about spirituality are implicated when providing clinical interventions for distressing voice hearing. Future research could explore further the differences between voices associated with spiritual experiences and "psychosis."